(untitled) (Research, Society and Development, 2021)
Pesticides or pesticides are considered chemical substances that act in the environment, in order to control different elements that harm the cultivation of crops or pastures, generally being used by occupational workers at rural level in order to increase production and eradicate diseases and pests existing. Many workers do not know how to correctly handle the application, purchase, dilution and disposal of agrochemicals. Thus, this research aims to discuss the main changes in biomarkers triggered by exposure of rural workers to pesticides. As a methodology, this study is a narrative review, carried out between the months of August and December 2020. The data collection was not based on the restriction of the year of publication of the studies found. The databases used were: National Center for Biotechnology Information (PUBMED); Scientific Electronic Library Online (SCIELO); Latin American and Caribbean Literature on Health Sciences (LILACS); trusted sites; books. The present research shows that the monitoring of biomarkers of exposure to pesticides can be useful to verify the appearance of physiological dysfunctions in exposed populations. It is noteworthy that the biomarkers most used for the evaluation of workers exposed to pesticides would be the enzymes acetylcholinesterase erythrocyte (AChE) and butyrylcholinesterase (BuChE), as well as the process of exposure to pesticides triggers a series of physiological reactions at the nervous level, decreasing, mainly, the action of the enzyme acetylcholinesterase, which in turn is responsible for the breakdown of excess acetylcholine.